2015
DOI: 10.1124/mol.115.099143
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inhibition of Phosphoinositide 3-Kinase/Mammalian Target of Rapamycin Sensitizes Pancreatic Cancer Cells to Doxorubicin without Exacerbating Cardiac Toxicity

Abstract: Pancreatic cancer has the lowest 5-year survival rate of all major cancers despite decades of effort to design and implement novel, more effective treatment options. In this study, we tested whether the dual phosphoinositide 3-kinase/mechanistic target of rapamycin inhibitor BEZ235 (BEZ) potentiates the antitumor effects of doxorubicin (DOX) against pancreatic cancer. Cotreatment of BEZ235 with DOX resulted in dose-dependent inhibition of the phosphoinositide 3-kinase/mechanistic target of rapamycin survival p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Over 50 days, our numerical results regarding the increase in tumor volume show a consistency with the experimental work (Durrant et al. 2015 ).…”
Section: Numerical Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Over 50 days, our numerical results regarding the increase in tumor volume show a consistency with the experimental work (Durrant et al. 2015 ).…”
Section: Numerical Resultssupporting
confidence: 89%
“…( 6 )), where ; b A comparison of numerical results with experimental results referring to (Durrant et al. 2015 ), where control and gem in the legend denote tumor growth without drug and with gemcitabine drug, respectively. In the simulation with curve 1, and are equal and 0.94, respectively.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a series of critical pathophysiological events of cardiovascular complications, endothelial dysfunction may cause hemorrhage, infarction, atherosclerosis, restenosis (Soultati et al, 2012;Wojcik et al, 2015). Studies have shown that Dox could downregulate CX40 (Idris-Khodja et al, 2013), MnSOD expression and activity (Koka et al, 2010;Santos-Alves et al, 2019), regulate Bcl-2/Bax ratio (Durrant et al, 2015;You et al, 2019), promote the shift from topoisomerase II a to II b (Deng et al, 2014;Damiani et al, 2018), disturb microRNA, DNA methylation or protein acetylation (Nordgren et al, 2017;Ferreira et al, 2017), affect PARP-2/SIRT (Szántó et al, 2011), VEGF pathway (Chiusa et al, 2012), and interfere with tight junction formation between cardiac microvascular endothelial cells leading to increased permeability (Wilkinson et al, 2016). In the study, we proved in vivo that, after injected Dox with the classical protocol, the mice showed the LDH and CK activities in serum increased significantly (Figures 2A, B), the inflammatory changes were observed by histopathology ( Figure 2C), which was noticeable as brown TUNEL-positive cells in microscopy ( Figure 2D).…”
Section: Discussionmentioning
confidence: 99%
“…The main side effect of Dox is cardiotoxicity, which can be drastically reduced by encapsulation in a polyethylene glycol (PEG)-coated liposome or by other nano-formulations 18 . However, Dox has low response rates in pancreatic cancer when used as a single agent because of acquired resistance 19 and limited penetration 19 21 . In the present study, the potential therapeutic strategy of a combination of nano-sized PEG-PCL-Dox micelles and GDC-0449 was investigated in pancreatic cancer in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%